URGENSI ANALISIS KESALAHAN BERBAHASA DALAM IMPLEMENTASI KURIKULUM 2013 - Ghufron, Syamsul (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
The curriculum in 2006 led to the notion that aspects of language does not need to be taught, whereas grammatical / linguistic competence covered in communicative competence. Therefore, aspects of language should be taught primarily to correct students' language errors. Based on such ideas, Indonesian student teachers need to be equipped by Language Error Analysis subject. This study aims to reveal the existence of Language Error Analysis subject and describe the urgency of Language Error Analysis subject in the implementation of 2013 curriculum. To achieve these objectives descriptive-qualitative research with documentation and interviews as data collection techniques were applied. The research subjects were lecturers of education majoring Indonesian language and literature. The results showed that Language Error Analysis course was still very necessary and the existence was urgent for the implementation of 2013 curriculum.